2021
DOI: 10.3906/tar-2006-100
|View full text |Cite
|
Sign up to set email alerts
|

Characterization of Fusariumsambucinum isolates associated with potato dry rot and evaluation of cultivar susceptibility and fungicides

Abstract: and Salas, 2001). The disease occurs in warehouses. 1 Dry rot disease affects both tubers in the warehouse and seed tuber parts in the field economically (Wharton et al., 2007). The disease begins primarily on the tubers in the form of dark and sunken superficial spots. In tuber flesh, necrotic areas are observed in colors ranging from light brown to black (Figure 1). When the rot progresses, gaps form in the tuber and tuber surface wrinkles.The disease reduces yield, seed quality and marketable product. It c… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(13 citation statements)
references
References 19 publications
1
10
0
Order By: Relevance
“…This percentage shows that Fusarium head blight is a cosmopolitan fungal disease that significantly affects the potato crop in the Far North Region, Cameroon. These results are in agreement with the work of [13,14] who reported that in Great Britain, the national average incidence of affected tubers was as high as 1.4% and 50-100%. Furthermore, [15] also showed that more than 50% of tubers are infected by Fusarium in Michigan; it is 43.7% in the Oued Tafna region of Algeria [34].…”
Section: Discussionsupporting
confidence: 93%
See 4 more Smart Citations
“…This percentage shows that Fusarium head blight is a cosmopolitan fungal disease that significantly affects the potato crop in the Far North Region, Cameroon. These results are in agreement with the work of [13,14] who reported that in Great Britain, the national average incidence of affected tubers was as high as 1.4% and 50-100%. Furthermore, [15] also showed that more than 50% of tubers are infected by Fusarium in Michigan; it is 43.7% in the Oued Tafna region of Algeria [34].…”
Section: Discussionsupporting
confidence: 93%
“…In addition, F. oxysporium, F avenaceum, F. equiseti, and F. solani have been recorded on potato by [17,24]. In Africa, Fusarium sambicum, F. oxysporium, predominate in Egypt [14]. The results of the morphological characterization of the colonies of the isolates grown on PPA, PCA, PSA and PDA culture media revealed that the majority of the colonies had a white colour, a regular growth, a cottony aspect on the different culture media with a relief varying from Flat to Domed.…”
Section: Discussionmentioning
confidence: 99%
See 3 more Smart Citations